2018
DOI: 10.1029/2018gc007645
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation of Mantle Viscosity and the Presence of Cratonic Mantle Inferred From 8 Years of Postseismic Deformation Following the 2010 Maule, Chile, Earthquake

Abstract: Postseismic displacements following great subduction earthquakes show significant long‐wavelength and time‐dependent patterns caused primarily by transient viscoelastic relaxation processes occurring broadly at depth. However, the Earth's viscosity structure and time‐dependent variations are still poorly understood, especially in the years immediately following a great earthquake. Here we investigate the spatiotemporal variation of mantle viscosity proximal and distal to the southern Andes using 8 years of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 55 publications
(136 reference statements)
4
23
1
Order By: Relevance
“…In addition to a Burgers body, a power law rheology has also been used to describe the temporal change of postseismic viscosity, which allows for a time‐dependent continuous increase of viscosity (Agata et al., 2019; Freed & Bürgmann, 2004; Kogan et al., 2013; Li et al., 2018; Qiu et al., 2018). By comparing the viscosity distributions at different times and regions, Li et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to a Burgers body, a power law rheology has also been used to describe the temporal change of postseismic viscosity, which allows for a time‐dependent continuous increase of viscosity (Agata et al., 2019; Freed & Bürgmann, 2004; Kogan et al., 2013; Li et al., 2018; Qiu et al., 2018). By comparing the viscosity distributions at different times and regions, Li et al.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the viscosity distributions at different times and regions, Li et al. (2018) found that the viscosities following the 2010 Maule earthquake increased with time and correlated with the temperature structure and stress state. Based on the power law rheology, Agata et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, space‐based geodetic systems, in particular Global Positioning System (GPS) and interferometric synthetic aperture radar (InSAR), have revolutionized our ability to monitor actively deforming areas with unprecedented spatial and temporal resolutions, revealing a wide spectrum of deformation processes that related to active tectonics on Earth (Bürgmann & Thatcher, 2013). Modeling of these geodetic observations has provided further insights into the fault kinematics and rheological structure at large‐scale fault systems in the different stages of earthquake cycle (e.g., Arnadóttir & Segall, 1994; Bürgmann & Dresen, 2008; Fialko, 2006; Freed et al., 2017; Hearn & Bürgmann, 2005; Itoh et al., 2019; Li et al., 2015; Li, Bedford et al., 2018; Pollitz, 2015; Qiu et al., 2018; Sato et al., 2010; T. Sun & Wang, 2015; K. Wang et al., 2012; Zhao et al., 2017). For the coseismic stage, surface deformation has been used to invert for the fault geometry (including its depth, strike, and dip angles) and slip distribution (i.e., earthquake source) of earthquakes at depth (e.g., Arnadóttir & Segall, 1994; Clarke et al., 1997; Reilinger et al., 2000; Simons et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
“…An entire earthquake process may contain three major phases: the inter-seismic accumulation, the co-seismic transient deformation, and the long-term post-seismic adjustment. The viscoelastic relaxation deformation, as a major mechanism of the post-seismic phase, can be captured using modern geodetic technologies for megathrust earthquakes (e.g., Wang et al 2012;Sun et al 2014;Li et al 2018;Qiu et al 2019;Agata et al 2019). To explain the multiple observations and investigate the physical mechanisms, accurate modeling for such processes is a necessity and attractive to geophysicists and geodesists.…”
Section: Introductionmentioning
confidence: 99%